Geographic/conceptual delimitation of the «Southern Mediterranean». A Regional Security Complex? (Comillas Journal of International Relations, 2016)
This article seeks to analyse how the Mediterranean Area has evolved after the changes occurred with the so-called Arab Springs. The main idea is to focus on the Southern Mediterranean as a dynamic space that expands itself as a result of its internal transformations and subsequent external changes caused by the Arab Spring. We will use the IR theory of the Regional Security Complex as it is considered as the most adaptable to this changing reality.
Keywords: Southern Mediterranean; Arab Spring; Regional Security Complex